The need for service change and community outreach work to support trans-cultural cognitive behaviour therapy with Black and Minority Ethnic communities. (15th January 2019) - Beck, Andrew; Naz, Saiqa
Abstract: Recently there have been a number of developments in cognitive behaviour therapy (CBT) that have led to cultural adaptations of specific interventions and a greater awareness of how in general CBT might be adapted for Black and Minority Ethnic (BME) service users. These developments, however, involve change at the level of the individual therapist and particular treatment approach, but involve very few considerations of what needs to happen at the levels of teams or services in order to best meet the mental health needs of British South Asian and other BME populations. This paper summarizes the way that services need to understand how minority populations use services and how to involve those populations in developing services in order to ensure their needs are best met.